2020
DOI: 10.3389/fpsyt.2020.570570
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Sense of Agency as a State Marker of First-Episode Schizophrenia: A Large-Scale Follow-Up Study

Abstract: Background: Schizophrenia is often characterized by a general disruption of self-processing and self-demarcation. Previous studies have shown that self-monitoring and sense of agency (SoA, i.e., the ability to recognize one's own actions correctly) are altered in schizophrenia patients. However, research findings are inconclusive in regards to how SoA alterations are linked to clinical symptoms and their severity, or cognitive factors.Methods: In a longitudinal study, we examined 161 first-episode schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…They found that, although both groups experienced agency when consciously determining the final resting place of the square, the schizophrenia group were significantly less likely to experience agency when the final resting place was unconsciously primed by 17‐ms subliminal displays (Renes et al, 2013). These findings have been replicated by other researchers (Prikken et al, 2018), and this impaired sense of agency has also been shown to be present from very early on in the illness (Kozáková et al, 2020).…”
Section: Alterations Of Self‐awareness In Clinical Conditionssupporting
confidence: 69%
“…They found that, although both groups experienced agency when consciously determining the final resting place of the square, the schizophrenia group were significantly less likely to experience agency when the final resting place was unconsciously primed by 17‐ms subliminal displays (Renes et al, 2013). These findings have been replicated by other researchers (Prikken et al, 2018), and this impaired sense of agency has also been shown to be present from very early on in the illness (Kozáková et al, 2020).…”
Section: Alterations Of Self‐awareness In Clinical Conditionssupporting
confidence: 69%
“…Excessive emotional resonance with others and arising difficulties with self-other distinction could have a broader effect on conscious experience of cognitive mental states including judgments about the origin of these. Difficulty knowing whether a thought or intention arose from the self explains many symptoms of psychosis [e.g., ( 155 )] including delusions relating to thought transfer and telepathy. Incorrect assumptions that one is aware of the cognitive mental state of another could also reduce mentalizing leading to egocentric errors ( 289 ).…”
Section: Relevance Of Self-other Distinction To Psychiatrymentioning
confidence: 99%
“…A possible explanation for this mixed/inconsistent association between symptomatology and agentic experience is the relationship between stage of illness progression and severity of altered agency. Although the number of studies investigating this relationship are limited, three studies have suggested a unified story that agency alterations increase across stage of disorder from prodromal ultrahigh risk (where negative symptoms and attenuated positive symptoms predominate the clinical presentation) to the acute phase of first-episode psychosis (where previously attenuated symptoms have crystallized into full-blown positive and negative psychotic symptoms) (Wilquin and Delevoye-Turrell, 2012;Kozáková et al, 2020;Nelson et al, 2020). The severity of altered agency appears related to the severity of positive symptoms reflected by stage of illness.…”
Section: Discussionmentioning
confidence: 99%